Active Fe2O3 nanoparticles encapsulated in porous g-C3N4/graphene sandwich-type nanosheets as a superior anode for high-performance lithium-ion batteries. Issue 27 (24th June 2016) - Shi, Minjie; Wu, Tianhao; Song, Xuefeng; Liu, Jing; Zhao, Liping; Zhang, Peng; Gao, Lian
Abstract : A novel composite anode of active Fe2 O3 nanoparticles encapsulated in g-C3 N4 /graphene hybrid nanosheets has been developed for high-performance lithium-ion batteries. Abstract : Designing sandwich-like hybrid nanosheets with a porous structure effectively improves the electrochemical performance of graphene-based materials in lithium-ion batteries (LIBs) owing to the mitigated restack of graphene and decreased diffusion distance of Li + ions for electron storage. Herein, a novel composite of active Fe2 O3 nanoparticles encapsulated in g-C3 N4 /graphene hybrid nanosheets (Fe2 O3 /CN–G) has been developed, in which the 2D sandwich-type hybrid nanosheets constructed using porous g-C3 N4 and highly conductive graphene offer readily accessible channels and sufficient conductive pathways for ionic diffusion and charge transport. This unique architecture greatly inhibits the restacking or aggregation of graphene and ensures the stability of electro-active Fe2 O3 nanoparticles. Benefiting from these intriguing features, the as-prepared Fe2 O3 /CN–G as an anode for LIBs shows excellent electrochemical behaviors, including considerably large reversible capacity (1023 mA h g −1 ), great coulombic efficiency (97.6%), strong durability and comparable rate performance. Therefore, the work described here can provide a new insight for designing high-performance electrode materials with a porous and sandwich-type hybrid structure for application in LIBs.